Study on awareness of human papillomavirus vaccine - P., Arunkumar; K., Kohila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer is the second most common cancer among women in India. Despite the various interventions, prevention is always better than cure. vaccination is the most effective way of preventing it. The objective of this study was to assess the knowledge, attitude and practice related to HPV vaccination among adolescents and reproductive age women. Methods: The data collected were used for the study. It was a community based cross sectional study involving 201 women as study participants who attended the obstetrics and gynecology department of Saveetha Medical College Hospital during the period of January 2022-March 2022 using a pretested, semi structured questionnaire tool. Results: Among the study population, 64.7% had knowledge about cervical cancer and 62.2% knew about vaccines and their effects. More than 60% of the study population were willing to get vaccinated. Conclusions: As a primordial prevention, we should create awareness among young population to get vaccinated against HPV, and sexually active women to take pap smear. This will prevent the incidence of cervical cancer in India.